Tinjauan Hukum Ekonomi Syariah Terhadap Praktik Jual Beli Dengan Fluktuasi Harga pada Sistem Pembayaran DP di Kopontren Al Mubarok Desa Pringgondani Kec. Sumberjambe - Fawaid Fawaid; Moh. hariyanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
This study aims to explain the views of Islamic economic law on the practice of buying and selling with price fluctuations in the DP payment system at Kopontre Al Mubarok, Pringgondani Village, Kec. Sumberjambe. This study uses a qualitative approach. This type of research is in the form of field research. The location of this research is in the Al Mubarok Kopontren, Pringgondani Village, Kec. Sumberjambe. Determination of informants using purposive. Data collection techniques use observation, structured interviews and documentation. The data analysis uses data condensation, data presentation and conclusions. While the validity of the data using source triangulation techniques and technical triangulation. The results showed that the practice of buying and selling with fluctuations in consumer prices first made transactions between the kopontren managers and consumers for the goods being traded and the payment was using DP. In terms of sharia economic law, the practice of buying and selling with price fluctuations in the DP payment system at Al Mubarok Kopontren Pringgondani Village is permissible (legal), because according to the theory of compilation of sharia economic law (KHES) the pillars and conditions in articles 56-57 are fulfilled.